Tensile properties of ytrium iron garnet (y3fe5O12) - thermoplastic natural rubber (TPNR) composites / Abdul Aziz Mansor and Siti Atkah Abdul Hamid - Mansor, Abdul Aziz; Abdul Hamid, Siti Atkah (2003)
Y3Fe5O12 (YIG) - thermoplastic natural rubber (TPNR) magnetic composites with 0 - 30 weight percent of YIG filler were prepared via Brabender plasticorder internal mixer. Blending conditions at 170°C with rotor speed of 50 rpm for 12 minutes. The microstructural and filler distribution in the PPINR matrix were performed via X-ray diffractometer (XRD) and thermogravimetric analyzer (TGA). The result of X-ray diffraction (XRD) indicates that the structure of YIG in the composites does not change after mixing in PPINR matrix. Thermogravimetric analysis confirmed the uniform dispersion of the YIG filler in the PPINR matrix. The tensile properties were determined via a universal testing machine. The result shows that the Young Modulus increase, but the maximum strain and the strain at break decrease, with filler content. The tensile properties of the composite are influenced by the filler contents.